Influence of Various Desensitizing Mouthrinses and Simulated Toothbrushing on Surface Roughness and Microhardness of Tetric N-Ceram Bulk-Fill Resin Composite: An In Vitro Study and Scanning Electron Microscope Analysis - Gehlot, Paras Mull; Sudeep, Parvathi; Manjunath, Vinutha; Annapoorna, B.M.; Prasada, L. Krishna; Nandlal, Bhojraj (European Journal of Dentistry, 2022)
Objectives Bulk-filled composite resins are popularly used for posterior restorations due to various advantages. Routine oral hygiene measures like toothbrushing and the use of various mouthrinses can influence the mechanical properties of composite resins. Desensitizing mouthrinses are widely used as well, to manage dentinal hypersensitivity. Studies on the influence of desensitizing mouthrinses on bulk-filled composites are limited. Hence, the objective of the present in vitro study was to evaluate the influence of toothbrushing and various desensitizing mouthrinses on the surface roughness and microhardness of Tetric N-Ceram bulk-fill composite resin.Materials and Methods Fifty Tetric N-Ceram bulk-fill composite resin disks were prepared and were randomly divided into five groups (n = 10). Group 1 (Control): no toothbrushing and no mouthrinse; Group 2: toothbrushing only; Group 3: toothbrushing + HiOra-K mouthrinse; Group 4: toothbrushing + Listerine Sensitive mouthrinse; and Group 5: toothbrushing + Shy-OR mouthrinse. The specimens were brushed with a soft bristle brush using a toothpaste slurry and immersed in respective mouthrinse twice daily for 1 month. The mean surface roughness (average roughness) and microhardness (Vickers Pyramid number) values were determined and the data were tabulated. Data were analyzed using one-way analysis of variance, Post-hoc Tukey test, and Pearson correlation test. A p-value less than 0.05 was considered statistically significant.Results Specimens treated with HiOra-K mouthrinse exhibited maximum surface roughness (p < 0.05) and specimens treated with Listerine Sensitive exhibited the least microhardness (p < 0.05). A weak negative correlation was found between surface roughness and microhardness for groups 1, 2, and 5, while a weak positive correlation was found for groups 3 and 4.Conclusions It is suggested that desensitizing mouthrinses containing alcohol or essential oils can lead to increased surface roughness and reduction in microhardness of bulk-fill composites, which could have an undesirable effect on their clinical performance.
Keywords: bulk-fill; direct composite resins; mouthrinses; desensitizer; surface roughness; microhardness